Upaya Meningkatkan Kemampuan Membaca Permulaan dengan Media Kartu Kata Bergambar pada Siswa Kelas 1 SD N Kategan Pundong Bantul - Sumiyati Sumiyati (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2019)
This research is kind of an action research. The aim is to know increasing students’ reading inception by using card picture colour media is done entitled “Effort of increasing students reading inception by using card picture colour media of the first grade students of SD N Kategan Pundong Bantul in the academic year of 2018/2019”. Teaching learning process by using card colour media is effective to increase students inception reading by the first grade students of SD kategan Pundong Bantul. The result shows ability average score is 14,73 ( earlier 65,13 to 79,86). the number of criteria completness minimum score KKM is increase 44% or 9 students ( earlier score is 43% to 87%. The result of the research is appropriate of standard criteria is determined by average score class of 75 and average completneess score is 75 %.